Dimer-Specific Potentiation of NGFI-B (Nur77) Transcriptional Activity by the Protein Kinase A Pathway and AF-1-Dependent Coactivator Recruitment - Maira, Mario (American Society for Microbiology, 2003)
The NGFI-B (Nur77) subfamily of orphan nuclear receptors (NRs), which also includes Nurr1 and NOR1, bind the NurRE regulatory element as either homo- or heterodimers formed between subfamily members. These NRs mediate the activation of pituitary proopiomelanocortin (POMC) gene transcription by the hypothalamic hormone corticotropin-releasing hormone (CRH), an important link between neuronal and endocrine components of the hypothalamo-pituitary-adrenal axis. CRH effects on POMC transcription do not require de novo protein synthesis. We now show that CRH signals activate Nur factors through the cyclic AMP/protein kinase A (PKA) pathway. CRH and PKA rapidly increase nuclear DNA binding activity of NGFI-B dimers but not monomers. Accordingly, CRH- or PKA-activated Nur factors enhance dimer (but not monomer) target response elements. We also show that p160/SRC coactivators are recruited to Nur dimers (but not to monomers) and that coactivator recruitment to the NurRE is enhanced in response to CRH. Moreover, PKA- and coactivator-induced potentiation of NGFI-B activity are primarily exerted through the N-terminal AF-1 domain of NGFI-B. The TIF2 (SRC-2) glutamine-rich domain is required for this activity. Taken together, these results indicate that Nur factors behave as endpoint effectors of the PKA signaling pathway acting through dimers and AF-1-dependent recruitment of coactivators.